Faktor-Faktor Yang Memengaruhi Struktur Modal Dengan Inflasi Sebagai Variabel Moderasi - Thalia Pricilla, Jonnardi (Jurnal Paradigma Akuntansi, 2022)
The purpose of this empirical study is to analyse the influence of liquidity, profitabilitity, growth opportunity, and total assets turnover on capital structure with inflation as a moderator in mining companies that were listed on the Indonesia Stock Exchange. The population used in this research were 47 mining companies that have been and are still listed in the Indonesia Stock Exchange in the year of 2014-2019. Sampling was selected using purposive sampling method and in this study a sample of 32 companies was obtained with a total of 138 data observation after outlier was done. This study use secondary data from audited financial statements and annual reports that were published on the Indonesia Stock Exchange official website. Data analysis technique used in this study was multiple regression analysis. The results of this research showed that total assets turnover has no significant effect on capital structure. On the other hand, the other variables such as liquidity, profitability and growth opportunity have a significant effect on the capital structure. Furthermore, inflation was proven to be able to strengthen the effect of profitability on capital structure. The implication of this study is the importance of the role company managers to determine optimal capital structure in order to maximize the company’s ability to generate profits, company growth and investor welfare.